2020
DOI: 10.1039/d0cc00027b
|View full text |Cite
|
Sign up to set email alerts
|

A BODIPY-based fluorescent sensor for the detection of Pt2+ and Pt drugs

Abstract: A novel BODIPY-based fluorescent sensor PS was designed for imaging Pt2+, cisplatin and nedaplatin in aqueous medium and biological environments, providing great potential for studying the Pt-drug metabolism and the development of new platinum drugs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
12
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(14 citation statements)
references
References 50 publications
1
12
0
1
Order By: Relevance
“…Although there have been advances in the treatment of HCC patients, the worldwide recurrence and mortality rates of HCC and HCC-associated cases are very high. NDP is a broad-spectrum antitumor drug, and it may be used in the treatment of malignant tumors, such as cervical, nasopharyngeal, esophageal, and lung cancer [24][25][26][27][28]. In recent years, a number of studies have shown that the molecular mechanism of NDP in tumors, and this potentially involved multiple potential mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Although there have been advances in the treatment of HCC patients, the worldwide recurrence and mortality rates of HCC and HCC-associated cases are very high. NDP is a broad-spectrum antitumor drug, and it may be used in the treatment of malignant tumors, such as cervical, nasopharyngeal, esophageal, and lung cancer [24][25][26][27][28]. In recent years, a number of studies have shown that the molecular mechanism of NDP in tumors, and this potentially involved multiple potential mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Our group developed several rhodamine‐based fluorescent turn‐on and ratiometric probes equipped with dithiocarbamates as recognition motifs to study the intracellular activation of Pt IV carboxylate prodrug complexes [9] . Leung and co‐workers also developed a BODIPY‐based probe for fluorescence imaging of cDDP [10] . However, these probes lack organelle‐targeting abilities and cannot be applied to study cDDP accumulation in mitochondria.…”
Section: Figurementioning
confidence: 99%
“…Luminescent molecular sensors are one of the most prominent among currently used in situ property measurement technologies [1][2][3][4][5][6]. Fluorescent probes demonstrate both intense callback and high versatility, due to the vast range of possible fluorescence quenching mechanisms.…”
Section: Introductionmentioning
confidence: 99%